An exploratory analysis of the effects of the formalisation policy for individual micro-entrepreneurs - Carlos Henrique L. Corseuil; Marcelo Neri; Gabriel Ulyssea (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
This paper presents an exploratory analysis of the potential impacts of the Lei do Empreendedor Individual (Individual Entrepreneur Law). We intend to present evidence that helps clarify, albeit only partially, whether the policy was successful in promoting: i) micro-entrepreneurship in Brazil; and ii) the formalisation of entrepreneurs. Regarding the promotion of micro-entrepreneurship, there is evidence that the policy may have achieved this particular goal. It is worth noting, however, that the evidence in this study suggests that larger businesses could be reducing their scale in order to fit within the programme requirements, as well as there being a possibility that certain companies, particularly smaller ones, might be using the programme to change their working relationships with their employees, from wage-earning work to services rendered. The policy seems to have had a positive effect on the formalisation of individual entrepreneurs in terms of social security contributions, but not in the rate of registration in the National Register of Legal Entities (CNPJ).
Keywords: L26; O17; 330; Exploratory Analysis; Effects; Formalisation; Policy; Individual Micro-Entrepreneurs; entrepreneurship; informality